Other anticipated architectures. A journey through the subsoil, soil and sky of New York - Carrascal Pérez, María Fernanda (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2013)
In the seventies, art called alternative or marginal was identified by an intensely urban stage. In New York, as an artistic epicenter, new places for creation were tested: urban investigations that delved into the different strata of the city. This spacial interpretation of the artists in this period concluded in projects in which new considerations of time and memory converged. The brief or continuous duration of these interventions was a strategy of action that allowed an instantaneous relationship with its immediate environment. Futhermore, this approach to daily life lead to the transformation of obsolete urban entities through criticism and symbolic production. In parallel to these new spaces for creative expression, their artists took on a responsibility in building a new way of conceptualizing the city of New York. This article is an overview of the history of some of these investigations and urban searches that, as immaterial and anticipated architectures, revealed another equation for the rehabilitation of the future city. For this purpose, a vertical mapping has been used, where the subsoil, soil and sky are the strata from which these projects of site reinvention are explained.